Generalized aggressive periodontitis in prepubertal age: description and comparison of two cases - G. Piergallini; A. Malerba; L. Mazzucchelli; L. Strohmenger (PAGEPress Publications, 2014)
Aggressive periodontitis is a rare form of periodontal disease and it can involve both the deciduous dentition and the permanent one. It causes a rapid loss of periodontal attachment. The paper aims to describe two cases of severe generalized prepubertal periodontitis: the first child doesn't suffer from neither systemic diseases nor alteration of functionality of polymorphonuclear and periodontal disease involved both his deciduous dentition and the first permanent molars. The second child had a deficiency of functionality of polymorphonuclear but periodontal disease involved only primary dentition thanks to his immediate improvement of home dental hygiene. This comparison shows the importance of early diagnosis and especially of optimal dental oral hygiene. Infant healthcare professionals, as pediatric dentists and pediatricians, should have the necessary knowledge for early and correct diagnosis and clinical management of disease.